The Level of Fraud Detection Affected By Auditor Competency Using Digital Forensic Support - SUSANTO, H.; MULYANI, S.; AZHAR AZIS, H.; SUKMADILAGA, C. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The authority of the BPK RI is to perform the Audit of Financial Statements. An investigation audit is conducted to reveal strong indications of fraud that have resulted in state losses and/or criminal elements. Given the increasing use of digital equipment to conceal the fraud, digital forensic support in detecting fraud is increasingly needed at this time. This study is based on the phenomenon of investigation audit quality, which is still not following the expectations of the stakeholders. This study aims to analyze how the competence of auditors and digital forensic support can increase the detection of fraud. RESUMEN La autoridad de BPK RI es realizar la Auditoría de Estados Financieros. Se realiza una auditoría de investigación para revelar fuertes indicios de fraude que han resultado en pérdidas estatales y / o elementos criminales. Dado el uso cada vez mayor de equipos digitales para ocultar el fraude, en este momento se necesita cada vez más apoyo forense digital para detectar el fraude. Este estudio se basa en el fenómeno de la calidad de la auditoría de investigación, que todavía no sigue las expectativas de los interesados. Este estudio tiene como objetivo analizar cómo la competencia de los auditores y el soporte forense digital puede aumentar la detección de fraude.